The transition of online into limited English learning-teaching in the rural area context - Amira Wahyu Anditasari; Siti Kholija Sitompul (JOALL (Journal of Applied Linguistics and Literature), 2022)
The Covid-19 pandemic has started to decrease, thus many schools in Indonesia have switched their learning activity from online to limited offline learning teaching. This new learning policy from the government might lead to the betterment or instead create new learning issues. Reflected from the online learning implementation, rural students suffer more compared to urban students. Therefore, this study aimed at exploring rural students’ perceptions towards the transition of online into offline limited learning teaching. A survey study was carried out in the state junior high school 3 Purbatua, North Sumatra, involving 49 students from level 7 to 9 grades. The students were provided with a close-ended questionnaire investigating their perceptions in terms of course content coverage, learning effectiveness, and learning interaction. This turned out that most students were less satisfied with the conductivity of limited offline teaching. Students’ satisfaction in the limited offline teaching needs to be considered to have an effective teaching and learning atmosphere. This might be beneficial both to the government and teachers as a reflection to maintain a more appropriate limited offline teaching. The learning and teaching barriers in turn might serve as a reflection for teachers to design more effective teaching activities.